SMARTRECRUITERS - Igilikov, Adilkhan; Yersultanov, Daniyar; Sakko, Talant; Bolat, Kassymkhan (Nazarbayev University School of Engineering and Digital Sciences, 2025)
The "SmartRecruiters" project presents a comprehensive recruitment management platform designed to automate and enhance the hiring process while promoting fairness and transparency. Existing systems often overlook junior-level candidates and rely on manual resume screening, which leads to inefficiencies and biased selections. SmartRecruiters addresses these issues through a custom-built CRM platform that integrates AI-driven tools such as automated test generation, and candidate status tracking. Developed using Java Spring Boot, Django REST, React/Next.js, and PostgreSQL, and deployed via Docker, the platform achieved high performance and usability scores in offline evaluations. The project demonstrates how AI and modern software practices can be combined to build ethical and efficient recruitment solutions, with future plans for real-world deployment, mobile support, and advanced analytics.
Keywords: Automated Recruitment; Fairness in Hiring; AI & NLP; Recruitment CRM Platform; Semantic Resume Matching; Agile Software Development; type of access: open access